The future of organizational design: A forecasting study - (:unkn) unknown (My University, 2012)
Teknolojik gelişmelerin hızıyla orantılı şekilde günden güne küreselleşen dünyada, işletme alanında öngörü (gelecek tahmin) çalışmalan önem kazanmıştır. Özellikle bilgi ve iletişim teknolojileri, işletmeleri ve faaliyette bulunduktan çevreyi hızla değiştirmektedir. Bu nedenle yöneticiler de, hızla değişen rekabet ortamında kararlarını gelecek ihtimallerini de göz önünde bulundurarak verme ihtiyacı hissetmektedir. Çalışmanın temel amacı geleceğin örgütlerini tanımlayabilmektir. Başka deyişle amaç, gelecek 10 yılda örgüt tasarımı boyutlarındaki değişimleri uzmanların fikirleri doğrultusunda tahmin edebilmektir. Günümüzde örgüt tasarımını etkileyen en önemli unsur teknolojidir. Bu nedenle çalışmada da teknolojinin geleceğin örgüt tasarımındaki etkisi göz önüne alınmıştır. Gelecek 10 yılda geleceğin örgütleri ise karmaşıklık, merkeziyetçilik ve formalizasyon boyutlarıyla ele alınmıştır. Çalışmada uzman görüşleri temel alınarak yapılan gelecek tahmin yöntemlerinden biri olan delfi metodu kullanılmıştır. Delfi ifadeleri önçalışma verilerine dayanarak ve altı akademisyenden oluşan bir ekip yardımıyla oluşturulmuştur. Delfi uzmanları bilgi teknolojilerinin etkisini göz önünde alabilmek için, Türkiye'de de faaliyet gösteren Dünya lideri bir teknoloji ve yönetim danışmanlığı firması çalışanlarından seçilmiştir. Sonuç olarak, stratejik bir araç olarak insan kaynağının artan önemine ters düşen sonuçlar elde edilmiştir. Beklenenin aksine geleceğin örgütlerinin daha merkezi ve formalizasyon düzeylerinin yüksek olacağı öngörülmüştür. Ayrıca işletmeye hızlı iletişim ve entegrasyon gibi avantajlar sağlayan benzer bilgi ve iletişim teknolojilerinin (SAP, Oracle vb.) kullanımının; işletmelerde, sektörden bağımsız şekilde, küresel boyutta bir benzeşme (izomorfizm) yaratma eğiliminde olduğu öngörülmüştür.

Forecasting (future studies in business) is gaining importance worldwide. As the world becomes increasingly global, technological developments have led to increasing uncertainty day by day. Technology, especially information technology, is changing business and its environment. Managers need to consider future possibilities for making decisions in a competitive environment. The main purpose of this study is to anticipate the future of organizational design based on expert predictions about changes in the dimensions of organizational design over the next decade. Nowadays, the most important factor to influence organizational design is technology, so this study tries to forecast the future of organizational design and taking the influence of information technology into consideration. The future of organizational design over the next ten decade is analyzed in terms of complexity, centralization and formalization. In this study, the Delphi method is used to analyze the experts' opinion about the future. When formulating the Delphi statements, preliminary study's results was used and also worked as a team with six academics. The sample of experts used in the study consisted of consultants working for a world-leading technology and management consultancy company operating out of Turkey. This selection was made because it was the neccessary to take the effects of information technology on organization. As a result, an organization design is forecasted that differs from what is found in studies forecasting that innovation and human resources as a strategic toll will increase in importance. In contract to what was thought, it is forecasted that in the future organization design will be more centralized with higher degrees of formalization. Furthermore, it is forecast that the use of similar information technology infrastructures (SAP, ORACLE etc.) brings companies many advantages, such as ease of communication, integration etc. and that companies, regardless of sector, are in many ways tending towards isomorphism.
Geleceğin örgüt tasarımı. Bir öngörü çalışması
Keywords: İktisat; İşletme